Benefits and Role of Carbon Dioxide Angiography in Case of Misalignment Between Fenestration and Target Vessel During Fenestrated Endovascular Aneurysm Repair. (February 2022) - Chisci, Emiliano; Michelagnoli, Stefano; Masciello, Fabrizio; Turini, Filippo; Panci, Simone; Troisi, Nicola
Purpose: To report the benefits and the role of carbon dioxide (CO2 ) angiography in case of misalignment between fenestration and target vessel during fenestrated endovascular aneurysm repair (F-EVAR). Technique: During F-EVAR, misalignment between fenestration and target vessel is a potentially catastrophic complication. In 2 patients, we experienced that one of the target vessels were not visible during standard angiography in different projections after positioning a fenestrated graft and even after cannulation of the corresponding fenestration. In both cases, the graft was sealed to the aortic wall but not in the predictable position. Consequently, acute occlusion of the target vessel was hypothesized. However, CO2 angiography was useful to evaluate patency of the target vessel clarifying the relative position of the fenestration versus the target vessel. Rescue maneuvers were feasible under the guidance of CO2 angiography in order to obtain the cannulation of both renal arteries. In both cases, the procedure was successfully accomplished. Conclusion: In case of misalignment of a fenestration during F-EVAR and non-visualization of the target vessel with standard angiography, CO2 angiography could have the unique and complementary role of clarifying the patency and position of the target vessel. In addition, CO2 could guide the rescue maneuvers.